MODELLING OF STRASS-STAIN STATE IN EPICENTRAL ZONE OF STRONG EARTHQUAKE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article describes the results of modeling the stress-strain state of the epicentral earthquake zone, which occurred on December 26, 2003 in the southeast of Iran in the province of Kerman (Bam), before and after the formation of the fault. It is shown that the main earthquake shock is located in the zone of high intensity of stresses, and the formed fault traces this zone on the surface and corresponds to its extent. Aftershocks are localized in the area of the maximum released stress intensity after the formation of the fault. Stress release stimulates the discharge of accumulated tectonic stresses in the subsequent aftershock process. The results obtained can be useful for deterministic approach to assessment and prediction of seismic hazard, as well as for geophysical observations clearly suited for the goal of predicting strong crustal earthquakes in continental regions.